Bubble breakup characteristics of Rushton turbine and curve blade impellers - Abdul Raman, Abdul Aziz; Vasanthi, S.; Ibrahim, Shaliza; Nik Sulaiman, N.M. (2004)
The objective of this work was to study the effects of impeller type and rotational speeds on bubble size for Ruston Turbine (6RT) and Six Bladed Curve Blade impeIler (6CB) in an agitated air-water system. NaCl (salt) was added to the water as anti-coalescence media. An aeration rate of 5 and 10 Umin and impeIler speeds of 60, 80 and 100 rpm was used for this purpose. 100 bubbles were sampled around the impeIler region and analysed for bubble size distribution (BSD) and Sauter mean diameter (d32). In all cases, BSD curves obtained were almost like a Gaussian distribution, with deviations from the symmetry. Bubbles with size in between 1.0 to 8.0 mm diameter were generated for both cases. At constant aeration rate, the d32 decreases when the impeIler speed increases for 6RT. Bubbles size with d32 values in between the range of 4.1 to 3.0 and 4.8 to 4.3 were obtained for respective aeration rate of 5 and 10 Umin for 6RT. On the other hand, at 5 Umin 6CB produces smaller bubbles at lower speed (60 rpm) where d32 of 3.7 was obtained. When the impeller speed was increased, d32 range of 4.3 to 4.7 was obtained.However at 10 Umin the d32 values remain almost constant at about 4.2 for all the impeller speeds investigated. The results show that the bubble size distribution is greatly dependent on type of impeller, speed and aeration rate for 6RT but for 6CB the bubble size distribution was effected by impeller speed only at lower gas rates. At higher gas rate,the d32 was not affected by the impeller speed. Further work is required to ascertain the reasons for these observations.